2018
DOI: 10.5205/1981-8963-v12i11a236650p3110-3124-2018
|View full text |Cite
|
Sign up to set email alerts
|

Intercorrências e cuidados a idosos em unidades de terapia intensiva

Abstract: RESUMOObjetivo: analisar as intercorrências clínicas e os cuidados prestados a idosos em Unidades de Terapia Intensiva. Método: trata-se de estudo bibliográfico, descritivo, tipo revisão integrativa com busca de artigos publicados entre os anos de 2007 a 2017, na base de dados LILACS e Bibliotecas SciELO e BVS. Utilizou-se no processo de análise estatística descritiva por meio de frequências e percentuais. Resultados: selecionaram-se 19 publicações. Apresentaram-se os idosos mais suscetíveis às infecções, prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
(22 reference statements)
0
3
0
6
Order By: Relevance
“…As for the older adult patient, a qualitative study revealed that there are several obstacles to be overcome to improve care for older adult patients in the ICU, such as inadequate environments, lack of resources, and lack of knowledge and skills ( 33 ) . It is noticed that the changes related to aging associated with the worsening of clinical conditions resulting from chronic diseases have increased the incidence of hospitalizations of the older adults ( 34 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the older adult patient, a qualitative study revealed that there are several obstacles to be overcome to improve care for older adult patients in the ICU, such as inadequate environments, lack of resources, and lack of knowledge and skills ( 33 ) . It is noticed that the changes related to aging associated with the worsening of clinical conditions resulting from chronic diseases have increased the incidence of hospitalizations of the older adults ( 34 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Diverse review studies point out the importance of the care provided to these patients, given the susceptibility to infections, vulnerability to incidents such as falls, and increased anxiety due to the prolonged hospital stay. Another finding is a gap in the production of research studies that seek to investigate nursing care for the older adult hospitalized in the ICU, in order to contribute to the robustness of the research on the theme and to the improvement of the care practice ( 34 - 35 ) .…”
Section: Discussionmentioning
confidence: 99%
“…A maioria dos idosos cardiopatas que se encontram internados na UTI, possuem uma instabilidade hemodinâmica instável, pela gravidade de seu diagnóstico, ocasionando consequentemente riscos de ocorrer a qualquer momento uma intercorrência. As doenças cardiovasculares em especial, deterioram muito a pessoa idosa que já se faz vulnerável pelo processo de envelhecimento, ocasionando os principais declínios súbito do órgão e sua função (SANTOS AM, et al, 2018).…”
Section: "[] Teimosia E Parâmetros De Ssvv Descompensados" (Enf 3)unclassified
“…O aumento global do número de idosos vem acompanhado de declínio funcional e vulnerabilidade a condições crónicas (Oliveira et al, 2018). Tal, resulta numa procura crescente por serviços de saúde, principalmente internamentos nas unidades de terapia intensiva (UTI), pois muitas vezes as doenças que atingem os idosos exigem cuidados intensivos com recurso a tecnologias mais complexas (Santos et al, 2018). No Brasil, os idosos são responsáveis por 42 a 52% dos internamentos em UTI.…”
unclassified
“…É um direito do idoso a satisfação das suas necessidades biopsicossociais, o respeito, o bem-estar e o conforto (Cardoso, Pacheco, et al, 2019). Entretanto, estudos apontam carências na assistência ao idoso hospitalizado (Carvalho et al, 2018;Faria et al, 2018;Santos et al, 2018). Promover conforto é um processo que vai além de posicionar o paciente adequadamente, aliviar a dor, assegurar a alimentação ou higiene (Kolcaba, 2003).…”
unclassified